1996
DOI: 10.1155/1997/205938
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Blind Prospective Randomized Study Comparing Topical Mupirocin and Placebo for the Prevention of Infection Associated with Central Venous Catheters

Abstract: These findings suggest that patients receiving topical mupirocin at the exit site for long term central venous catheters have significantly less local catheter-related infection, and there is a trend towards less catheter-related bacteremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…The study was designed to include only patients in whom a central line was likely to be inserted for 172 h. Previous data suggested that such patients could be determined 190% of the time before line insertion [29]. However, 35% of enrolled patients in our study had a central line inserted for !72 h and were excluded from the primary analysis.…”
Section: Discussionsupporting
confidence: 83%
“…The study was designed to include only patients in whom a central line was likely to be inserted for 172 h. Previous data suggested that such patients could be determined 190% of the time before line insertion [29]. However, 35% of enrolled patients in our study had a central line inserted for !72 h and were excluded from the primary analysis.…”
Section: Discussionsupporting
confidence: 83%